P528 Reducing intravenous monoclonal antibody observation times without compromising patient safety; a single-centre observational study. (27th May 2021) - Rees, F; Packham, A; Parmar, A; Hills, E; Smith, M; St. Clair Jones, A
Abstract: Background: Monoclonal antibodies (MAbs) are integral to manage Inflammatory Bowel Disease (IBD). At Brighton & Sussex University Hospitals, intravenous MAbs, infliximab and vedolizumab, are administered in an outpatient setting. Licensing specifies post-infusion observation times of 1 to 2 hours. This affects waiting lists and capacity, particularly pertinent during the COVID-19 pandemic. Methods: A single-centre observation study was conducted. Part 1 Retrospective data was collected for all infliximab and vedolizumab infusions from April to July 2019. Patients seen twice, were included once. For established infusion patients, historical reactions were recorded. Reaction incidence was established by observations, patient questioning and patient record review. To standardise the reactions, we used the cancer Common Terminology Criteria for Adverse Events; grade 3 is 'severe'. Part 2 Observation time was removed from infusion 4 in April 2020. Prospective data was collected for all infliximab and vedolizumab infusions from April to December 2020. Multiple attendances were included. Results: Part 1 130 infliximab patients (2607 infusions) and 69 vedolizumab patients (557 infusions) were reviewed. No severe reactions were recorded. All reactions occurred during induction dosing period. Analysis showed high levels of 'no reactions observed' after the first 4 infliximab infusions 97.7% (+1.6%, -4.7%), and the first 3 vedolizumab infusions 96.9% (+2.3%, -8.8%). 121 hours could be saved for infliximab and 64 hours for vedolizumab. Extrapolated this equates to 740 hours per year. Part 2 679 infliximab infusions were administered (including 12 new starters). 418 vedolizumab infusions were administered (16 new starters). No reactions were reported. Table key: Pt – patients, Inf – infusions, MAb – monoclonal antibody, Induct – Induction, Maint – maintenance, IV – intravenous, PO – oral, NC – not collected Conclusion: All MAb infusion reactions occurred within 3 infusions, were non-severe and managed in clinic. By removing observation periods from infusion 4, capacity increased in concordance with COVID-19 social distancing, without affecting waiting times or patient safety. Patient experience was anecdotally improved. Further data from other centres are required to prove significance.